COLLABORATIVE GOVERNANCE DI MASA KRISIS: UPAYA PERCEPATAN PELAYANAN VAKSINASI COVID-19 DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Umi Lestari; Adji Suradji Muhammad (Governance, 2023)
The purpose of this study is to identify and discuss collaborative governance during times of crisis at the local level by taking case studies of accelerated COVID-19 vaccination services in the Province of the Special Region of Yogyakarta (DIY). Collaborative governance of accelerating COVID-19 vaccination in DIY involves government actors, both central and regional governments, entrepreneurs including corporations on various scales from international, regional, national and local as well as business associations, as well as civil society with a membership base that varies from professional expertise to religion. This study used a qualitative method with data collection carried out through a desk study. Collaborative governance allows the exchange of resources between actors that are cross-sectoral and the flexibility of mobility between actors to accelerate people's access to vaccines as a public good. Collaborative governance is a potential solution for building and developing a better service system for public needs.